2014
DOI: 10.5433/1679-0359.2014v35n5p2551
|View full text |Cite
|
Sign up to set email alerts
|

Etiologia e fatores de risco para a infecção mamária de cabras leiteiras em seis propriedades do Estado de São Paulo

Abstract: ResumoO objetivo do trabalho foi identificar os agentes etiológicos e fatores de risco para a mastite carpina. Para tanto, foram colhidas duas alíquotas de 257 amostras de leite, nos meses compreendidos entre Abril a Setembro de 2012, provenientes de 136 cabras da raça Saanen, oriundas de seis criações intensivas, com sistema de ordenha manual e mecânica, localizadas no estado de São Paulo. A primeira alíquota das amostras de leite foi obtida em frascos contendo o conservante bronopol para a contagem de célula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
1
2
2
Order By: Relevance
“…In this study, we found 27.7% (46/166) of CNS isolates, and differing from studies performed in other regions of Brazil, where they found CNS in 83.3% (Neves et al 2010) and 79.7% of isolates in the Northeast region (Cavalcante et al 2013), and 62.2% ) and 90.5% (Gomes et al 2014) in the Southeast region. In Brazil, only phenotypic methods have been used in the identification of bacterial species from caprine mastitis samples in the studies published so far.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In this study, we found 27.7% (46/166) of CNS isolates, and differing from studies performed in other regions of Brazil, where they found CNS in 83.3% (Neves et al 2010) and 79.7% of isolates in the Northeast region (Cavalcante et al 2013), and 62.2% ) and 90.5% (Gomes et al 2014) in the Southeast region. In Brazil, only phenotypic methods have been used in the identification of bacterial species from caprine mastitis samples in the studies published so far.…”
Section: Discussioncontrasting
confidence: 99%
“…The risk factors found for mastitis in this study differed from those found in the few similar studies done in Brazil (Neves et al 2010, Gomes et al 2014). These studies relate to risk factors for caprine mastitis in the northeast region of the country, where the breeds, management and climatic conditions are different.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The identification of the non-aureus Staphylococci group was performed by the macroscopic and microscopic evaluation of the colonies, catalase and coagulase tests; RapID identification systems (Remel-Oxoid) were also used for Staphylococcus aureus; and the catalase test and macro and microscopic identification of the colonies were performed for Corynebacterium spp. (GOMES et al, 2014). The results obtained for the microbiological examination were distributed in score 0 (negative) and score 1 (positive).…”
Section: Methodsmentioning
confidence: 99%
“…Excessive vacuum, failure or absence on the pulse, inappropriate pulsation rate and intervals between milking shorter than 10 h increase the intensity of tissue damage and reduce the strength of the teat channel by compromising the physical defense mechanism (LU et al, 1991;ALEJANDRO et al, 2014a). In addition, the lack of hygiene in the milking process represents a risk factor for caprine mastitis (WÓJTOWSKI et al, 2006;GOMES et al, 2014).…”
Section: Introductionmentioning
confidence: 99%